La-MIL88B (Fe) bimetal organic framework material containing oxygen vacancies as well as preparation method and application of La-MIL88B (Fe) bimetal organic framework material

By preparing the La-MIL88B(Fe) bimetallic organic framework material with oxygen-containing vacancies, the problems of low efficiency and poor selectivity in water phosphate removal are solved, and efficient and economical phosphate removal effect is achieved.

CN119529311AInactive Publication Date: 2025-02-28BEIJING FORESTRY UNIVERSITY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510099252.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems such as low treatment efficiency, poor selectivity, high energy consumption and secondary pollution when removing phosphate in water bodies, which is difficult to meet increasingly stringent environmental protection requirements and diversified wastewater treatment needs.

Method used

The material was prepared by solvothermal reaction using the La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies, and its structure and adsorption properties were optimized by adjusting the substance ratio of La/Fe.

Benefits of technology

The material exhibits high adsorption capacity, fast adsorption rate, good selectivity and a wide range of pH application in water phosphate removal, and is low in cost and can be reused multiple times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529311A_ABST
    Figure CN119529311A_ABST
Patent Text Reader

Abstract

The invention discloses a La-doped oxygen vacancy-containing La-MIL88B (Fe) bimetal organic framework material as well as a preparation method and an application of the La-doped oxygen vacancy-containing La-MIL88B (Fe) bimetal organic framework material. The preparation method comprises the following steps: mixing and dissolving ferric chloride hexahydrate, lanthanum chloride heptahydrate and terephthalic acid in an organic solvent, and then carrying out solvothermal reaction to obtain the oxygen vacancy-containing bimetallic La-MIL88B (Fe) organic framework material. The material is the material prepared by the method. According to the application, the materials are adopted to remove phosphate in water in a static adsorption and / or dynamic adsorption mode. The preparation method disclosed by the invention is simple and low in cost, and the prepared La-MIL88B (Fe) material can be used for removing phosphate in water and has the characteristics of high dynamic adsorption capacity, relatively high adsorption rate, high selectivity, wide pH application range and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a La-MIL88B (Fe) bimetallic organic framework material containing oxygen vacancies, a preparation method and an application thereof. Background Art

[0002] With the acceleration of industrialization and urbanization, the problem of eutrophication of water bodies is becoming increasingly serious. Among them, phosphorus is one of the main nutrients. Excessive discharge into water bodies will lead to excessive algae growth, thus causing a series of environmental problems, such as eutrophication of water bodies, fish deaths and water quality deterioration. Therefore, how to effectively remove phosphorus from wastewater has become a research focus in the field of environmental science and engineering. Traditional phosphorus removal methods include chemical precipitation, ion exchange and biological treatment. Although these methods have unique characteristics and have been applied in various adaptive occasions and achieved corresponding positive effects, they still generally have problems such as low treatment efficiency, poor selectivity, high energy consumption and secondary pollution, which makes it difficult to meet the increasingly stringent environmental protection requirements and diversified wastewater treatment needs. In particular, in practical applications, due to the complex composition of wastewater and large pH fluctuations, the applicability and effectiveness of traditional methods are greatly limited. Therefore, it is necessary to further develop products to increase adsorption capacity, increase the adaptability range to pH, and enhance selectivity for high phosphates.

[0003] In recent years, metal organic frameworks (MOFs) have gradually attracted people's attention due to their high specific surface area, adjustable structure and multifunctionality. This type of material has shown broad application prospects in the fields of gas storage, catalysis and adsorption separation. However, the adsorption performance and selectivity of single metal MOFs materials need to be improved. Summary of the invention

[0004] The purpose of the present invention is to provide a La-MIL88B (Fe) bimetallic organic framework material containing oxygen vacancies and a preparation method and application thereof, which can be used to remove phosphate in sewage and take into account the various requirements of preparation cost and use performance in practice.

[0005] The technical solution of the present invention is: a method for preparing a La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies, wherein a metal salt and a ligand are used as raw materials, dissolved together in an organic solvent, and a solvothermal reaction is performed to obtain the La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies, wherein the metal salt is ferric chloride hexahydrate and lanthanum chloride heptahydrate, and the ligand is terephthalic acid.

[0006] Furthermore, after the solvothermal reaction, the reaction product (solid) is sequentially washed and dried.

[0007] Furthermore, the organic solvent is NN dimethylformamide.

[0008] Preferably, after the metal salt and the ligand are dissolved in an organic solvent, ultrasonic dissolution is first performed, and then a solvothermal reaction is performed.

[0009] Preferably, the ratio of the amount of La to the amount of Fe in the raw material (excluding the organic solvent, the same below) is 0.25 to 2 (including the end values, the same below), for example, 0.25, 0.5, 0.75, 1, 1.5 or 2.

[0010] Furthermore, the molar ratio of La to Fe in the raw material (excluding the organic solvent) is 1.

[0011] Preferably, the ratio of the amount of the metal salt (two metal salts in total) to the amount of the ligand in the raw material is 0.5 to 5, for example, 0.5, 1, 1.5, 2, 3, 4 or 5.

[0012] Furthermore, the ratio of the amount of the metal salt to the amount of the ligand in the raw material is 1.

[0013] Preferably, the ultrasonic dissolution time can be 5 to 10 min, for example, 5 min, 6 min, 7 min, 8 min or 10 min.

[0014] Preferably, the reaction temperature of the solvothermal reaction is preferably 80 to 160°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 140°C or 160°C, and the reaction time is 8 to 24 h, for example, 8 h, 10 h, 12 h, 16 h, 20 h or 24 h.

[0015] Furthermore, the temperature of the solvothermal reaction is 110-160°C.

[0016] Furthermore, the temperature of the solvothermal reaction is 110°C.

[0017] Furthermore, the reaction time of the solvothermal reaction is 12 h.

[0018] Preferably, the solvent thermal reaction is carried out in a polytetrafluoroethylene reactor.

[0019] Preferably, the washing is performed by sequentially washing with N-N-dimethylformamide, ethanol and water; Preferably, the washing method is shaking centrifugal washing.

[0020] Preferably, the oscillation time of the oscillating centrifugal washing is 1 to 5 min, for example, 1 min, 2 min, 3 min, 4 min or 5 min, and the centrifugal speed is 4000 to 8000 r / min, for example, 4000 r / min, 5000 r / min, 6000 r / min or 8000 r / min.

[0021] Furthermore, the shaking time of the shaking centrifugal washing is 1 min.

[0022] Furthermore, the centrifugal speed of the oscillating centrifugal washing is 5000 r / min.

[0023] Preferably, the drying is carried out in a vacuum oven.

[0024] Preferably, the drying temperature is 50-110°C, for example, 50°C, 80°C, 100°C or 110°C; the drying time is 12-48 h, for example, 12 h, 18 h, 24 h, 36 h or 48 h.

[0025] Furthermore, the drying temperature is 60°C.

[0026] Furthermore, the drying time is 12 h.

[0027] The La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies is prepared by using any preparation method of the La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies disclosed in the present invention.

[0028] The invention relates to an application of any La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies disclosed in the present invention in removing phosphate from water or in a phosphate removal experiment in water; or, an application of any La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies prepared by the method for preparing any La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies disclosed in the present invention in removing phosphate from water or in a phosphate removal experiment in water, wherein the bimetallic organic framework material containing oxygen vacancies adsorbs phosphate in water, thereby achieving removal of phosphate (separation from water).

[0029] Furthermore, the adsorption method is static adsorption and / or dynamic adsorption.

[0030] Preferably, especially when applied to phosphate removal experiments in water, the static adsorption can be carried out in a constant temperature oscillation box.

[0031] Furthermore, the constant temperature oscillation box is a constant temperature air bath oscillation box or a constant temperature water bath oscillation box.

[0032] Preferably, the rotation speed of the constant temperature oscillating box is 100 to 200 r / min, for example, 100 r / min, 120 r / min, 160 r / min, 180 r / minn or 200 r / min Furthermore, the rotation speed of the constant temperature oscillation box is 160 r / min.

[0033] Preferably, especially when applied to phosphate removal experiments in water, the dynamic adsorption can be carried out in a plexiglass column.

[0034] Furthermore, the inner diameter of the plexiglass column can be 0.5 to 2 cm, for example, 0.5 cm, 0.8 cm, 1 cm, 1.5 cm or 2 cm, and the length can be 5 to 20 cm, for example, 5 cm, 8 cm, 10 cm, 15 cm or 20 cm.

[0035] Typically, the inner diameter of the organic glass column may be 1 cm and the length may be 5 cm.

[0036] Furthermore, the filling mass of the material (the bimetallic organic framework material of La-MIL88B(Fe) containing oxygen vacancies) can be 0.1 to 5 g, for example, 0.1 g, 0.5 g, 1 g, 1.5 g, 3 g or 5 g.

[0037] Typically, the filling mass of the material body used may be 1 g.

[0038] Preferably, during the dynamic adsorption, a peristaltic pump is used to maintain a constant flow rate.

[0039] Furthermore, the flow rate of the peristaltic pump can be 0.1 to 5 mL / min, for example, 0.1 mL / min, 0.5 mL / min, 1 mL / min, 3 mL / min or 5 mL / min.

[0040] Typically, the flow rate of the peristaltic pump may be 1 mL / min.

[0041] Preferably, the pH value of the water (phosphate-containing water to be treated) is 2 to 12, for example, 2, 4, 7, 10 or 12.

[0042] Furthermore, the water also contains Ca 2+ Mg 2+ , Cl - 、NO3 - 、HCO3 - 、CO32- 、SO4 2- , HA and FA, any one or more thereof.

[0043] The beneficial effects of the present invention are as follows: The preparation method of the present invention is simple, does not require high-end or complex equipment, and can reduce the preparation cost; Compared with existing adsorbents, the present invention has the advantages of large actual dynamic adsorption capacity, fast adsorption rate, high selectivity, and wide pH applicable range; The bimetallic doping design of the present invention, by doping with lanthanum, increases the competition between different metal centers and ligands during the synthesis of the crystal, generates abundant oxygen vacancy defects, and not only increases the phosphate adsorption capacity of the material, but also improves the selectivity of the material; The present invention allows the adjustment of the La / Fe material ratio. By adjusting the La / Fe material ratio, the structural morphology and adsorption performance of the material can be controlled, and the specific surface area and pore structure of the material can be optimized / selected; When the La-MIL88B(Fe) bimetallic MOFs material containing oxygen vacancies prepared by the present invention is used for adsorption of phosphate in actual sewage, it has a strong anti-interference ability to coexisting substances and can be regenerated and reused multiple times; The bimetallic La-MIL88B(Fe) material containing oxygen vacancies prepared by the present invention has a higher phosphate adsorption capacity than the monometallic MIL88B(Fe) material; The bimetallic La-MIL88B(Fe) material containing oxygen vacancies prepared by the present invention has a lower synthesis cost than the monometallic La-MOFs material.

[0044] The present invention effectively improves the structure of the MIL88B (Fe) material and the phosphate removal efficiency through the innovation of the preparation method, and can be used for phosphate removal in water including sewage, with significant ecological environmental protection benefits and practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Graph showing the adsorption capacity of xLa-MIL88B(Fe) and MIL88B(Fe) prepared in Example 1 and the control group for phosphate; Figure 2 XRD patterns of xLa-MIL88B(Fe) and MIL88B(Fe) prepared in Example 1 and the control group; Figure 3 SEM images of xLa-MIL88B(Fe) and MIL88B(Fe) prepared in Example 1 and the control group; Figure 4Oxygen vacancy maps of xLa-MIL88B(Fe) and MIL88B(Fe) prepared in Example 1 and the control group; Figure 5 This is the oxygen vacancy diagram of 1La-MIL88B(Fe) before and after phosphate adsorption in Example 2; Figure 6 The Langmuir adsorption isotherms of phosphate at different temperatures for 1La-MIL88B(Fe) and MIL88B(Fe) in Example 2; Figure 7 The Frendlich adsorption isotherms of phosphate by 1La-MIL88B(Fe) and MIL88B(Fe) at different temperatures in Example 2; Figure 8 The adsorption kinetics of phosphate by 1La-MIL88B(Fe) and MIL88B(Fe) in Example 2; Fig. 9 This is a diagram showing the adsorption effect of phosphate by 1La-MIL88B(Fe) under the coexistence of different substances in Example 3; Fig.10 This is a diagram showing the adsorption effect of phosphate by 1La-MIL88B(Fe) at different initial pH values ​​in Example 4; Fig.11 This is a graph showing the effect of the number of adsorption-desorption cycles of 1La-MIL88B(Fe) on the adsorption of phosphate in Example 5; Fig.12 N2- adsorption-desorption isotherms of xLa-MIL88B(Fe) and MIL88B(Fe) in Example 5; Fig.13 is the pore size distribution diagram of xLa-MIL88B(Fe) and MIL88B(Fe) in Example 5; Fig.14 The SEM-EDS images of 1La-MIL88B(Fe) before and after phosphate adsorption in Example 5; Fig.15 This is a diagram showing the dynamic adsorption effect of 1La-MIL88B(Fe) on phosphate solution in Example 6; Fig.16 This is a diagram showing the dynamic adsorption effect of MIL88B (Fe) on phosphate solution in Example 6; Fig.17 This is a diagram showing the dynamic adsorption effect of phosphate in the secondary effluent of a sewage treatment plant by 1La-MIL88B(Fe) in Example 6. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with specific implementation methods. The given examples are only for illustrating the present invention and do not constitute a limitation on the protection scope of the present invention.

[0047] The experimental methods in the following examples are all conventional methods unless otherwise specified.

[0048] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0049] xLa-MIL88B(Fe) is used to express La-MIL88B(Fe) with different La / Fe, where x represents the molar ratio of La and Fe in La-MIL88B(Fe) (or molar ratio, which can be expressed as La / Fe, or La:Fe). For example, 1La-MIL88B(Fe) means that the molar ratio of La and Fe is 1 (or 1:1).

[0050] The xLa-MIL88B(Fe) involved in the following embodiments includes: 0.25La-MIL88B(Fe), 0.5La-MIL88B(Fe), 0.75La-MIL88B(Fe), 1La-MIL88B(Fe), 1.5La-MIL88B(Fe), and 2La-MIL88B(Fe).

[0051] For the convenience of presentation, x = 0 corresponds to the prepared (or existing) MIL88B(Fe) in the control group.

[0052] Comparative example. Preparation of MIL88B(Fe) and its phosphate adsorption performance Step 1. Weigh the drugs: weigh 2.7030 g of ferric chloride hexahydrate and 1.6613 g of terephthalic acid; Step 2, dissolving the drugs: using a beaker, mix the above drugs and dissolve them in 50 mL of NN dimethylformamide (DMF), and ultrasonically dissolve them for 10 min to obtain a solution; Step 3, solvothermal reaction: transfer the above solution to a polytetrafluoroethylene reactor and react in an oven at 110 °C for 12 h; Step 4: Wash and dry the sample: After the reactor is cooled to room temperature, wash the material three times with DMF, ethanol and water respectively by oscillation and centrifugation. Dry the washed material in a vacuum oven for 12 h at 60 °C. Grind the dried material in a mortar and store it in a desiccator for later use. Step 5, adsorption experiment: potassium dihydrogen phosphate (KH2PO4) was used to prepare a phosphate solution with a concentration of 25 mg P / L for the adsorption experiment, and 9 mg of the MIL88B (Fe) material prepared above was weighed and applied to 30 mL of the phosphate solution, and then oscillated in a constant temperature water bath oscillator for 12 h at a speed of 160 rpm and a temperature of 25 °C; Step 6. Determination of phosphorus concentration: Use a disposable syringe to take a sample from the solution after the above reaction, filter it through a 0.45 𝜇m aqueous cellulose membrane, and then use a Hach spectrophotometer to determine the phosphorus concentration in the filtrate.

[0053] The experiment was repeated three times and the results were averaged to calculate the adsorption capacity.

[0054] Example 1. Preparation of xLa-MIL88B(Fe) and its phosphate adsorption performance Taking the preparation of 1La-MIL88B(Fe) and its phosphate adsorption performance as an example, the specific steps are as follows: Step 1. Weigh the drugs: weigh 1.5446 g of ferric chloride hexahydrate, 1.5916 g of lanthanum chloride heptahydrate and 1.6613 g of terephthalic acid; Steps 2 to 6 are the same as those in the control example, except that in step 5 the MIL88B(Fe) material used for adsorption is replaced by the 1La-MIL88B(Fe) material prepared in this example.

[0055] The experiment was repeated three times and the results were averaged.

[0056] Based on the same preparation and measurement method, while keeping the total amount of the two metal salts unchanged, the La / Fe (achieved by adjusting the ratio of ferric chloride hexahydrate and lanthanum chloride heptahydrate) was adjusted to 0.25, 0.5, 0.75, 1.5 and 2, respectively, to prepare 0.25La-MIL88B(Fe), 0.5La-MIL88B(Fe), 0.75La-MIL88B(Fe), 1.5La-MIL88B(Fe) and 2La-MIL88B(Fe) and measure the corresponding adsorption capacities.

[0057] The results are as follows Figure 1As shown in the figure, it can be seen that when the La:Fe (molar ratio) is 0 (corresponding to MIL88B(Fe) prepared in the control group), the adsorption capacity of MIL88B(Fe) on phosphate is 40.98 mg P / g. When the La:Fe molar ratio is 1:1, the adsorption capacity of phosphate by 1La-MIL88B(Fe) is 84.92% higher than that of MIL88B(Fe). However, when the La:Fe molar ratio continues to increase, the adsorption capacity of phosphate by the material increases slowly, and the adsorption capacity of 2La-MIL88B(Fe) only increases by 6.98% compared with 1La-MIL88B(Fe).

[0058] Figure 2 The XRD pattern of xLa-MIL88B(Fe) is shown in Figure 1. The peaks at 9.2° and 10.7° of the XRD spectrum of MIL88B(Fe) are respectively assigned to the (002) and (101) planes. When the molar ratio of La / Fe is 0.25, the peak of La-MIL88B(Fe) at 9.2° begins to shift to the right, and the peak intensity gradually decreases with the increase of lanthanum content. With the incorporation of La, the (101) plane of MIL88B(Fe) gradually disappears, indicating that La is successfully incorporated into MIL88B(Fe) to form a bimetallic organic framework material.

[0059] Figure 3 This is the SEM image of the above xLa-MIL88B(Fe). It can be clearly seen from the figure that the MIL88B(Fe) crystal maintains a complete spindle structure. As the La content increases, the structure of MIL88B(Fe) gradually disintegrates, and its morphology becomes irregular and broken, while the structure of La-MOF (block and rod) gradually becomes obvious. This is because with the addition of La, La competes with MIL88(Fe) for ligands, resulting in an incomplete structure during crystal growth, which in turn leads to the generation of defects and exposes more adsorption sites. This also shows that La is successfully incorporated into MIL88B(Fe), which is consistent with the results of XRD.

[0060] Figure 4This is the oxygen vacancy defect diagram in the above xLa-MIL88B(Fe). It can be clearly seen from the figure that there are no oxygen vacancy defects in the MIL88B(Fe) crystal, while La-MOF contains a small amount of oxygen vacancies, which shows that in the process of synthesizing La-MOF alone, the crystal will produce inherent defects. However, with the increase of La content, oxygen vacancies also appeared in La-MIL88B(Fe), and the content of oxygen vacancies was the largest when La / Fe was 1:1. This shows that in addition to the inherent defects generated by the bimetallic MOF during the synthesis process, the competition between La and Fe will also produce additional oxygen vacancies. This is conducive to the bimetallic MOF to produce more additional adsorption sites for the adsorption of phosphate, which can significantly increase the adsorption effect of phosphate.

[0061] Figure 5 The above diagram shows the oxygen vacancy defect of 1La-MIL88B(Fe) before and after the adsorption of phosphate. It can be clearly seen that the oxygen vacancy concentration after adsorption is significantly reduced compared with that before adsorption, which shows that oxygen vacancy defects play an important role in the adsorption process of phosphate. This is because the active sites mediated by oxygen vacancies can reduce the kinetic barrier and increase the adsorption rate by promoting the orbital bonding reaction of phosphate.

[0062] Example 2. Adsorption isotherm and adsorption kinetics of phosphate by 1La-MIL88B(Fe) 1. Adsorption isotherm Step 1: Use potassium dihydrogen phosphate (KH2PO4) to prepare phosphate solutions with concentrations of 5, 10, 15, 20, 25, 40, 60, 80, 100 and 200 mg P / L respectively; Step 2: 1La-MIL88B(Fe) was added to the above phosphate solutions of different concentrations at a dosage of 0.3 g / L, and adsorbed in a constant temperature water bath oscillating box for 12 h. The oscillating box speed was 160 rpm and the temperatures were 25 °C, 35 °C and 45 °C respectively. Step 3: Determination of phosphorus concentration is the same as step 6 in the control example.

[0063] The experiment was repeated three times and the results were averaged.

[0064] 2. Adsorption kinetics Step 1: Use potassium dihydrogen phosphate (KH2PO4) to prepare 1000 mL of a phosphorus solution with a concentration of 25 mg P / L. Take 30 mL of the phosphorus solution into 100 mL conical flasks, add 9 mg of 1La-MIL88B(Fe) at a dosage of 0.3 g / L, place the conical flask in a constant temperature water bath and oscillate for a certain period of time before sampling. The sampling time points are 1, 5, 10, 15, 20, 25, 30, 40, 50, 60, 90, 120, 180, 240, 300, 360, 480, 600, 720 and 1440 min, respectively. The oscillation box parameters are set as follows: speed 160 rpm, temperature 25 °C; Step 2: Determination of phosphorus concentration is the same as step 6 in the control example.

[0065] The experiment was repeated three times and the results were averaged.

[0066] Figure 6 and Figure 7 Figure 3 are the adsorption isotherms of phosphate on 1La-MIL88B(Fe) and MIL88B(Fe). The fitting results show that the adsorption of phosphate on the material is more consistent with the Langmuir model. 1La-MIL88B(Fe) has a larger adsorption capacity than the control MIL88B(Fe).

[0067] Figure 8 The adsorption kinetics of phosphate by 1La-MIL88B(Fe) and MIL88B(Fe) show that the adsorption of phosphorus by the materials is more consistent with the pseudo-second-order kinetic model.

[0068] Example 3. Adsorption performance of 1La-MIL88B(Fe) on phosphate under the coexistence of different substances Step 1: Use potassium dihydrogen phosphate (KH2PO4) to prepare a 25 mg P / L phosphorus solution containing cations Mg 2+ , Ca 2+ , anion Cl - 、NO3 - 、HCO3 - 、CO3 2- 、SO4 2- and organic matter HA and FA, which were prepared from MgCl2, CaCl2, NaCl, NaNO3, NaHCO3, Na2CO3, Na2SO4, HA-Na and FA, respectively, and the concentrations of coexisting ions were set to three gradients: 10 mg / L, 50 mg / L and 100 mg / L; Step 2: Add 1La-MIL88B(Fe) to the above phosphorus solution containing different coexisting substances (dosage is 0.3 g / L), and shake at 25 °C and 160 rpm for 12 h; Step 3: Determination of phosphorus concentration is the same as step 6 in the control example.

[0069] The experiment was repeated three times and the results were averaged.

[0070] Effects of coexisting substances on phosphate adsorption Fig. 9 As can be seen from the figure, the coexisting cations have no effect on the adsorption process of phosphate. As the concentration of the coexisting substances increases, the coexisting anions CO3 2- and HCO3 - There was a slight inhibitory effect on the adsorption process. The coexistence of HA and FA did not inhibit the adsorption of phosphate even at concentrations as high as 100 mg / L.

[0071] Example 4. Adsorption performance of 1La-MIL88B(Fe) on phosphate at different pH values Step 1: Use 0.1 M hydrochloric acid (HCl) and sodium hydroxide (NaOH) to adjust and prepare a series of 25 mg P / L phosphorus solutions (prepared with potassium dihydrogen phosphate) with different pH values ​​of 2, 4, 6, 7, 8, 10 and 12, respectively; Step 2: 1La-MIL88B(Fe) was added to the above phosphorus solutions with different pH values ​​(dosage: 0.3 g / L), and the mixture was shaken at 160 rpm and 25 °C for 12 h. Step 3: Determination of phosphorus concentration is the same as step 6 in the control example.

[0072] The experiment was repeated three times and the results were averaged.

[0073] Results Fig.10 It can be seen that 1La-MIL88B(Fe) has a high adsorption capacity for phosphorus in the pH range of 4 to 10, and has a more obvious adsorption capacity under acidic conditions. This is because the material has a strong protonation effect under acidic conditions, which in turn enhances the electrostatic adsorption effect on the surface of the positively charged material. Therefore, the adsorbent has a wide pH applicability.

[0074] Example 5. Effect of adsorption-desorption cycle number on the adsorption performance of 1La-MIL88B(Fe) phosphate Step 1: Add 0.3 g 1La-MIL88B(Fe) to 1000 mL of a solution with a phosphorus concentration of 25 mg / L (prepared with potassium dihydrogen phosphate), stir the reaction with a magnetic stirrer at 25 °C for 12 h, then use a disposable syringe to take 1 mL of the solution, filter it through a 0.45 𝜇m water system membrane, and use a Hach spectrophotometer to determine the phosphorus concentration in the filtrate. Filter the remaining solution to obtain a solid material, and dry it in a vacuum oven at 60 °C for 12 h; Step 2: Place the dried material in step 1 in 1000 mL of 5 M NaOH solution and shake at 160 rpm and 25 °C for 12 h to desorb phosphate. Then, filter the solution to obtain the desorbed solid material. Wash the obtained material to neutrality and place it in a vacuum oven at 60 °C for 12 h. Grind the dried material with a mortar and store it in a desiccator for later use. The desorbed material is then subjected to a phosphate adsorption experiment at 25 °C at a dosage of 0.3 g / L. Use a disposable syringe to take a sample from the solution after the above reaction, filter it through a 0.45 𝜇m water system membrane, and use a Hach spectrophotometer to determine the phosphorus concentration in the filtrate. Then, desorb the material with a 5 M NaOH solution and repeat the above steps.

[0075] The experiment was repeated three times and the results were averaged.

[0076] Fig.11 The effect of the number of adsorption-desorption cycles on the adsorption of phosphate by 1La-MIL88B(Fe) is shown. It can be seen from the figure that the adsorption performance of the material does not change much with the increase in the number of adsorption-desorption cycles, and can maintain a stable adsorption capacity within five cycles.

[0077] Fig.12 and 13 The specific surface area and pore size distribution diagrams of 1La-MIL88B(Fe) are shown in the figure. It can be clearly seen from the figure that with the increase of La content, the nitrogen adsorption of the material gradually decreases; and the incorporation of La has a significant effect on the pore structure of the material, and the addition of La reduces the porosity and specific surface area of ​​the material. This shows that the adsorption mechanism of the adsorbent for phosphate does not simply rely on physical adsorption (such as surface adsorption or pore adsorption), but involves chemical adsorption, charge interaction and other mechanisms.

[0078] Fig.14 This is the SEM-EDS image of 1La-MIL88B(Fe) before and after the adsorption of phosphorus. It can be clearly seen that the structure of the material is not destroyed after the adsorption, phosphorus is successfully adsorbed on the material, and the structure and crystallinity of the material do not change much before and after the adsorption, indicating that the material structure is stable.

[0079] Example 6. Dynamic adsorption performance of phosphate by 1La-MIL88B(Fe) and MIL88B(Fe) Step 1: Add 1 g of 1La-MIL88B(Fe) and control MIL88B(Fe) materials into organic glass columns. The specific dimensions of the glass columns are 1 cm in inner diameter, 5 cm in length, and the filler filling heights are 2 cm and 2.5 cm, respectively. A peristaltic pump is used to provide a constant flow of phosphate-containing aqueous solution at a flow rate of 1 mL / min. Step 2: Use 2 mg / L phosphate solution and 1.76 mg / L soluble phosphorus content of the secondary effluent of the sewage plant as feed solution. The water quality of the secondary effluent of the sewage plant is shown in Table 1. After the experiment started, the effluent was collected regularly, and the phosphorus concentration was measured using a Hach spectrophotometer after filtering through a 0.45𝜇m water system membrane. The interval time for collecting the effluent was 2 h; The experiment was repeated three times and the results were averaged.

[0080] Fig.15 and Fig.16 These are the dynamic adsorption effects of 1La-MIL88B(Fe) and the control MIL88B(Fe) on 2 mg P / L phosphate solution. It can be seen from the figure that 1 g of 1La-MIL88B(Fe) material can treat 4978 BV of bed volume of phosphate solution, making it meet the Class II water quality standard in the Surface Water Environmental Quality Standard (GB 3838-2002), and the effective treatment capacity is significantly higher than 651 BV of the control MIL88B(Fe).

[0081] Fig.17 The figure shows the dynamic adsorption effect of 1La-MIL88B(Fe) on phosphate in the secondary effluent of the sewage treatment plant. It can be seen from the figure that the adsorption capacity of 1La-MIL88B(Fe) on phosphate in the secondary effluent of the sewage treatment plant is as high as 5054 BV. This shows that although the actual sewage contains anions and cations such as sulfate, nitrate, calcium, magnesium and complex organic matter, 1La-MIL88B(Fe) still exhibits excellent phosphate adsorption effect and high phosphate adsorption selectivity.

[0082] Based on the same preparation and determination method as the above embodiment, the amount (ratio) of ferric chloride hexahydrate, lanthanum chloride heptahydrate and terephthalic acid is adjusted so that the ratio of the amount of metal salt (two metal salts in total) to the amount of ligand terephthalic acid is 0.5, 1, 1.5, 2, 3, 4 and 5 respectively, and several kinds of La-MIL88B (Fe) materials under the corresponding raw material ratio are obtained, and the adsorption capacity and other characteristics of these materials for phosphate are measured respectively. Relevant experiments show that these La-MIL88B (Fe) have good phosphate adsorption capacity and selectivity / specificity and other required characteristics, and can be used for the adsorption and separation of phosphate in water. When used for the secondary effluent of the above-mentioned sewage treatment plant, the treated effluent can meet the Class II water quality standard in the surface water environmental quality standard (GB 3838-2002). The existing research results on the preparation mechanism of MIL88B (Fe) / La-MIL88B (Fe) also support the change of the amount of ligand in this range.

[0083] Table 1 Water quality of secondary effluent from sewage treatment plant

Claims

1. A method for preparing a La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies, comprising taking a metal salt and a ligand as raw materials, dissolving them together in an organic solvent, and conducting a solvothermal reaction to obtain a La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies, wherein the metal salts are ferric chloride hexahydrate and lanthanum chloride heptahydrate, and the ligand is terephthalic acid.

2. The preparation method according to claim 1, characterized in that After the solvothermal reaction, the reaction product is sequentially washed and dried.

3. The preparation method according to claim 1, characterized in that After the metal salt and the ligand are dissolved in an organic solvent, ultrasonic dissolution is first performed, and then a solvothermal reaction is performed.

4. The preparation method according to any one of claims 1 to 3, characterized in that The organic solvent is NN dimethylformamide.

5. The preparation method according to any one of claims 1 to 3, characterized in that The ratio of the amount of La to the amount of Fe in the raw material is 0.25 to 2.

6. The preparation method according to any one of claims 1 to 3, characterized in that The ratio of the amount of the metal salt to the amount of the ligand in the raw material is 0.5 to 5.

7. A bimetallic organic framework material of La-MIL88B(Fe) containing oxygen vacancies, characterized in that The material is prepared by the method for preparing the La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies described in any one of claims 1 to 6.

8. Use of the La-MIL88B(Fe) bimetallic organic framework material containing oxygen vacancies as claimed in claim 7 in the removal of phosphate in water or in a phosphate removal experiment in water, wherein the bimetallic organic framework material containing oxygen vacancies adsorbs phosphate in water, thereby achieving the removal of phosphate.

9. The use according to claim 8, characterized in that The adsorption method is static adsorption and / or dynamic adsorption.

10. The use according to claim 8 or 9, characterized in that Water also contains Ca 2+ Mg 2+ , Cl - 、NO3 - 、HCO3 - 、CO3 2- 、SO4 2- , HA and FA, any one or more thereof.

Citation Information

Patent Citations

  • Method for removing arsenic by using carbon-based Fe / La-metal organic framework composite adsorbent

    CN118437298A

  • Eco-friendly resin composition comprising recycled polycarbonate resin and molded article for automobile parts using the same

    KR1020240159049A